The Influence of Individual Characteristics toward Benefit Recipients’ Participation of Program Keluarga Harapan - Nurwan, Tryas Wardani; Hasan, Helmi (International Journal of Educational Review, 2020)
The purpose of the study was to determine the effect of individual characteristic toward benefit recipients’ participation of Program Keluarga Harapan (PKH) in Nagari Pematang Panjang, Sijunjung District, West Sumatera. This study used quantitative method with a questionnaire and data analysis using SPSS 21. Based on Slovin’s theory, the respondents in this study were 131 from the 194 benefit recipients. Indicator variable Participation as the dependent variable is participation in the implementation of P2K2 and participation in taking PKH fund benefits. While the indicator variables of individual characteristics as independent variables are the level of education (X1), age (X2), and number of dependents of the Family (X3). The results showed that the three individual characteristic variables influence recipients’ participation.